2013
DOI: 10.1371/journal.pone.0078162
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Social Factors Associated with Late Pregnancy Iron Deficiency Anaemia in Rural Viet Nam: A Population-Based Prospective Study

Abstract: ObjectivesThe aim of this study was to examine the relationships between psychological and social factors and late pregnancy IDA among pregnant women in rural Viet Nam.MethodsPregnant women from 50 randomly-selected communes within Ha Nam province were recruited and assessed at 12 - 20 weeks gestation (Wave 1, W1). They were followed up in the last trimester (Wave 2, W2). IDA was defined as Haemoglobin < 11 g/dL and serum ferritin < 15 ng/mL. Symptoms of Common Mental Disorders (CMD) were assessed by the Edinb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 36 publications
0
63
0
1
Order By: Relevance
“…Four studies were observational prospective cohort studies . 13,17,18,19 One study was a case control study. 20 All 25 studies used faceto-face interviews or consultations to collect self-reported primary data from women using questionnaires.…”
Section: Study Design Source Of Data and Data Collection Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies were observational prospective cohort studies . 13,17,18,19 One study was a case control study. 20 All 25 studies used faceto-face interviews or consultations to collect self-reported primary data from women using questionnaires.…”
Section: Study Design Source Of Data and Data Collection Methodsmentioning
confidence: 99%
“…In four studies, clinical examination and/or laboratory tests were also conducted. 6,18,21,22 Three studies extracted data using secondary data analysis of large databases of hospital admissions, discharges or birth registers. 23,24,25 In these secondary data analyses authors used their own data collection tool, with little details of the variables extracted.…”
Section: Study Design Source Of Data and Data Collection Methodsmentioning
confidence: 99%
See 3 more Smart Citations